Effects of levothyroxine therapy on bone and mineral metabolism in hypothyroidism: a systematic review and meta-analysis - Xiaotao Li; Taotao Zhang; Hongling Zhang; Shanshan Liu; Limin Tian (BMC Endocrine Disorders)
Abstract Background Thyroid hormone plays an important role in accumulating bone development and regulating bone metabolism. It is established that hypothyroidism is linked to increased risk of osteoporosis and fracture. However, the effects of levothyroxine (LT4) treatment on bone for hypothyroid patients remain controversial. Methods A systematical search was conducted of several databases, from inception until December 9, 2022, and updated the search using the same search strategy on October 30, 2024, for studies evaluating the effects of LT4 treatment on bone in hypothyroidism including subclinical hypothyroidism (SCH) and overt hypothyroidism (OH). The data were reported using a random-effects model with a standardized mean difference (SMD) and 95% conference interval (CI). Results Thirteen of the 5996 published articles were included in this meta-analysis. No significance was found in bone mineral density (BMD) at the lumbar spine between SCH patients treated with LT4 and control group either at baseline or after intervention. For OH, BMD at the lumbar spine was statistically lower in LT4 treatment group compared with healthy controls (HCs) (SMD: -0.28, 95%CI: -0.55, -0.02, P = 0.040, I 2  = 52%). There were no differences in BMD at the femoral neck, trochanter, and Ward’s triangle between OH patients treated with LT4 and HCs. In addition, BMD at the lumbar spine was significantly lower in males with OH undergoing LT4 treatment for a duration of less than five years compared to those treated over five years. Nevertheless, no significant differences were found in bone metabolism biomarkers between OH patients treated with LT4 and HCs. Conclusion This systematic review and meta-analysis demonstrated that there is a slight adverse effect of LT4 replacement therapy on bone and mineral metabolism in patients with OH, while no observed effect was found in SCH patients.